PTU-257 "Trials and tribulations of setting up an anaesthetist led day-case endoscopy list". (28th May 2012) - Murugesan, S V; Davies, M; Haslam, N; Smart, H L; Sarkar, S
Abstract : Introduction: Endoscopy in UK is performed under conscious sedation in daycase (DC) endoscopy units. Patients intolerant of the procedure subsequently undergo the procedure under a general anaesthetic in operating theatres. However whether this service could be effectively offered in a "non-operating theatre room" setting through an anaesthetist-led sedation service (ALS) is not well established within the UK. Aim: To evaluate a new provision of an ALS in a day case endoscopy unit. Methods: Service evaluation audit (June–August 2011) of a new weekly dedicated ALS at the Royal Liverpool Hospital was performed. Administrative, anaesthetic and case records and satisfaction scores (1=unsatisfactory; 5=fully satisfied; patients, anaesthetists, endoscopists) and "patient journey" was evaluated. Results: Administration : Three cases were scheduled per listed. Waiting time was a median 9 weeks compared to a median 6 weeks for other lists. Of the 25 patients listed, only 20 (80%) had a procedure. DNA rate was 16% and cancellation rate 4%. Patients and Indication : Median age was 53 years (range 18–80 years), median ASA was 2 (range 1–3), 8 (42%) were female. 20 underwent propofol assisted endoscopy (7 colonoscopy, 8 HALO ®, 3 ERCP, 1 OGD and 1 EUS). Procedural details : ALS was provided by a consultant anaesthetist assisted by operating theatre personnel and endoscopic procedures by a consultant gastroenterologist. All were successfully completed (mean duration of 33 min, range 20–70 min). Modification of anaesthetic equipment was required in all but one and additional equipment had to be borrowed in all. Adverse events were minor (rate 10%)—transient hypoxia (not required ventilation) and hypotension. All patients were discharged successfully as DC. 7-day readmissions and 30-day mortality was 0. The median satisfaction score was 5 (range 4–5) for patients, 5 (range 4–5) for anaesthetists and 5 (3–5) for endoscopists. The additional cost for provision of such a service included the services of the anaesthetist (one programmed activity) and OTP and for drugs (propofol). Conclusion: Deep sedation for selected endoscopic procedures can be safely and efficiently provided through a dedicated anaesthetist-led list in a remote endoscopy unit. However, waiting times were longer than other lists and a significant number of patients DNA'd/cancelled. We are now setting up pre-assessment clinics and increasing the number of lists to improve the service further. Competing interests: None declared.